Perancangan Produk Interior Pelindung Gempa Bumi Pada Rumah Tinggal Satu Lantai - Kevin Jeremia; Grace Mulyono (Intra, 2019)
Indonesia is a country with multiple earthquake occure in a day, make collapsed buildings and Fatalities. As a reaction to this issue, the author will produce interior products which are expected to reduce the fatalities during earthquakes. After following the design method, the final design must be produced in full scale to test its quality as a facilities of earthquake protector. Principal of space frame is used in product because it has good rigid properties.